Rekonsiliasi joko widodo dan prabowo subianto pasca pemilu 2019 dalam pemberitaan detik.com, cnnindonesia.com dan viva.co.id periode 13-27 juli 2019 (Faculty of Communications Science, Dr. Soetomo University, 2019)
Indonesia just finished the very first simultaneous election in history of this country, without doubt the people attention of this election is concentrated to president and the vice president election. And after long, exhausting, and complicated election process, including appeal from Prabowo Subianto and Sandiaga Salahudin Uno side on Constitutional Court of Indonesia. Once again, Joko Widodo and Ma’ruf Amin has choosen as president and the vice of president for 2019-2024 period of Indonesia. Prabowo’s side has been reported still hard to admit his third defeat on president election and refuse to congratulate Jokowi for his second win on election. But finally the two sides of candidates that just fight election met on Lebak Bulus MRT station and media call this meeting as “reconciliation”. This study analyse the point of view of online media towards this event, and how media construct this event on 3 popular Indonesia online media, detik.com, cnnindonesia.com and vivanews.com using Pan Kosiciki framming analysis model. And the result those 3 online media construct this event in balanced manner eventhough they have their unique style to deliver the news. Keywords: Rekonsiliasi; Jokowi; Prabowo; Pemilu 2019; Media Online